2013
DOI: 10.1007/s00442-013-2816-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity of an invasive plant species promotes litter decomposition and associated processes

Abstract: Following studies that showed negative effects of species loss on ecosystem functioning, newer studies have started to investigate if similar consequences could result from reductions of genetic diversity within species. We tested the influence of genotypic richness and dissimilarity (plots containing one, three, six or 12 genotypes) in stands of the invasive plant Solidago canadensis in China on the decomposition of its leaf litter and associated soil animals over five monthly time intervals. We found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
0
9
0
1
Order By: Relevance
“…Further, strong selection that increases average carbon use efficiency (similar to what is expected by OU evolution) can weaken these relationships (Gravel et al 2012). While our results confirm that species' evolved differences contribute to ecosystem function, an additional factor that we did not consider is the role of intraspecific variability and plasticity in influencing ecosystem function (Burns and Strauss 2012, Violle et al 2012, Wang et al 2014. Work by Burns and Strauss (2011) has shown that closely related plant species are more likely to exhibit phenotypic plasticity, which contributes to their coexistence.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Further, strong selection that increases average carbon use efficiency (similar to what is expected by OU evolution) can weaken these relationships (Gravel et al 2012). While our results confirm that species' evolved differences contribute to ecosystem function, an additional factor that we did not consider is the role of intraspecific variability and plasticity in influencing ecosystem function (Burns and Strauss 2012, Violle et al 2012, Wang et al 2014. Work by Burns and Strauss (2011) has shown that closely related plant species are more likely to exhibit phenotypic plasticity, which contributes to their coexistence.…”
Section: Discussionmentioning
confidence: 49%
“…, Wang et al. ). Work by Burns and Strauss () has shown that closely related plant species are more likely to exhibit phenotypic plasticity, which contributes to their coexistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of plant genetic diversity on ecosystem processes may also be mediated by microbial and invertebrate composition and activity in the soil. Mixed-genotype plant litter has been shown to decompose faster than expected from the decomposition rates of single-genotype litters (Schweitzer et al, 2005;Wang et al, 2014). This effect has been attributed to resource complementarity whereby mixed litter provides a more complete range of substrates to a more diverse set of decomposers.…”
Section: Introductionmentioning
confidence: 99%
“…的 研 究 , 有 关 GD-EF 及 其 内 在 机 制 的 探 讨 较 少 (Hughes & Stachowicz, 2004;沈栋伟等, 2007) (Whitham et al, 2006;Bailey et al, 2009;Bailey, 2011;Hersch-Green et al, 2011) (Wolfe, 1985;Smithson & Lenné, 1996)。无独有偶, 保护生物学家 也在试图通过增加稀有物种种群的遗传多样性来提 高稀有物种种群的适合度 (Lande, 1988 (Loreau & Hector, 2001;Crutsinger et al, 2006;Johnson et al, 2006;Crawford & Rudgers, 2013;Wang et al, 2014;Hughes et al, 2016;申俊芳等, 2016) 基因丰富度 Allelic richness 所检测位点上等位基因的平均数目。 The average number of alleles detected at the detected locus.…”
unclassified